Body motion of choral singers - Sara D'Amario; Sara D'Amario; Sara D'Amario; Sten Ternström; Werner Goebl; Laura Bishop; Laura Bishop (Frontiers in Psychology, 2023)
Recent investigations on music performances have shown the relevance of singers' body motion for pedagogical as well as performance purposes. However, little is known about how the perception of voice-matching or task complexity affects choristers' body motion during ensemble singing. This study focussed on the body motion of choral singers who perform in duo along with a pre-recorded tune presented over a loudspeaker. Specifically, we examined the effects of the perception of voice-matching, operationalized in terms of sound spectral envelope, and task complexity on choristers' body motion. Fifteen singers with advanced choral experience first manipulated the spectral components of a pre-recorded short tune composed for the study, by choosing the settings they felt most and least together with. Then, they performed the tune in unison (i.e., singing the same melody simultaneously) and in canon (i.e., singing the same melody but at a temporal delay) with the chosen filter settings. Motion data of the choristers' upper body and audio of the repeated performances were collected and analyzed. Results show that the settings perceived as least together relate to extreme differences between the spectral components of the sound. The singers' wrists and torso motion was more periodic, their upper body posture was more open, and their bodies were more distant from the music stand when singing in unison than in canon. These findings suggest that unison singing promotes an expressive-periodic motion of the upper body.